Effect of Parigi Pineapple (Ananas Sp.) Juice Consumption on LDL Cholesterol Level in Students of Medical Faculty, University of Palangka Raya. - Sasmithae, Lia; Patricia, Tisha; Perdana, Indra (Nutrición Clínica y Dietética Hospitalaria, 2023)
Excessive consumption of cholesterol could increase the cholesterol level in the blood which is recognized as hypercholesterolemia. LDL (Low-Density Lipoprotein) is a dangerous type of cholesterol particle for the body. A non-pharmacology therapy that could decrease the cholesterol level in the blood is the consumption of Parigi pineapple fruit (Ananas sp.). Three primary contents of Parigi pineapple (Ananas Sp.): Vitamin C, Niacin, and Myricetin could fix the lipid profile. This quasi-experimental research aims to discover the effect of Parigi pineapple juice consumption on the LDL cholesterol level in the Faculty of Medicine Students, University of Palangka Raya. Methods : The design is one group pre-test and post-test with the sample in total of 43 male and female students from batch 2020 Faculty of Medicine, University of Palangka Raya, selected through convenience sampling. The tools are Cobas C111, centrifuge cholesterol-checking devices, and juice-making tools such as knife, scales, measuring cylinder, blender, glass, and gloves. Results: After the consumption of Parigi pineapple juice (Ananas Sp.) for 6 days with the dose of 142 gr/70 kg, the data were calculated using the Wilcoxon test with α = 0.05 and p= 0.000. The average LDL cholesterol level dwindled from 118.7 mg/dl to 102.53 mg/dl. Conclusion: The treatment could be developed as non-pharmacology therapy since it is proven capable of decreasing LDL cholesterol level.